Impact of socratic teaching on pharmacy students’ critical thinking and patient-centredness regarding emergency contraception - Hope, D.; King, M.; Hattingh, H. Laetitia (International Pharmaceutical Federation, 2017)
© 2017 FIP.Introduction: Pharmacists’ timely provision of emergency contraception (EC) requires critical thinking and a sensitive patient-centred approach. Aim: To explore the impact of Socratic teaching on pharmacy students’ professional judgement, critical thinking and patient-centredness, in relation to EC provision. Methods: One hundred and fifty-three first and second year graduate entry Master of Pharmacy students, representing pre-and post-EC teaching groups, were presented with a questionnaire comprising an array of challenging hypothetical scenarios involving pharmacy requests for EC. Results: One hundred and forty-two (92.8%) students responded. First and second year students showed significant differences in their intentions to supply EC or refer to another health professional. Student comments demonstrated differences in both social and professional judgement pre-and post-teaching. Justifications provided to explain their choices indicated that post-teaching students better understood that context impacts on decision making, especially when delivering patient-centred care. Conclusion: Socratic teaching enhances students’ critical thinking and patient-centredness in relation to hypothetical EC provision.